2016
DOI: 10.1371/journal.pone.0150532
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis as a Comorbidity of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis

Abstract: BackgroundBronchiectasis revealed by chest computed tomography in COPD patients and its comorbid effect on prognosis have not been addressed by large-sized studies. Understanding the presence of bronchiectasis in COPD is important for future intervention and preventing disease progression.MethodsObservational studies were identified from electronic literature searches in Cochrane library, PubMed, ScienceDirect databases, American Thoracic Society and European Respiratory Society meeting abstracts. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 41 publications
3
63
1
9
Order By: Relevance
“…Although the presence of bronchiectasis in patients with COPD is usually associated with chronic bronchial infection and more frequent exacerbations, mostly of a bacterial etiology,25,31,32 this infective component is not adequately covered by the usual treatment for COPD based on inhaled therapy with bronchodilators, with or without inhaled corticosteroids (ICS). Some recent studies have demonstrated that even patients on triple therapy may suffer from frequent exacerbations 45.…”
Section: Bronchiectasis In Copd: Therapeutic Consequencesmentioning
confidence: 99%
“…Although the presence of bronchiectasis in patients with COPD is usually associated with chronic bronchial infection and more frequent exacerbations, mostly of a bacterial etiology,25,31,32 this infective component is not adequately covered by the usual treatment for COPD based on inhaled therapy with bronchodilators, with or without inhaled corticosteroids (ICS). Some recent studies have demonstrated that even patients on triple therapy may suffer from frequent exacerbations 45.…”
Section: Bronchiectasis In Copd: Therapeutic Consequencesmentioning
confidence: 99%
“…Recent research has revealed the importance of extrapulmonary effects on treatment, and the contribution of comorbidities, to the overall severity of COPD (Vogelmeier et al, 2017). Much of the financial cost associated with COPD treatment is related to common systemic comorbidities, which are thought to be part of organ-specific inflammatory processes, for example, respiratory inflammation, cardiovascular disease and, most commonly, periodontitis (Du et al, 2016). Microorganisms are thought to be one of the main etiologic factors that exacerbate COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory comorbidities associated with COPD include bronchiectasis,6 asthma, pulmonary fibrosis,7 and lung cancer,7 but extra thoracic chronic inflammatory disease also co-occurs 8. Cardiovascular diseases are the most common,9 including hypertension,7 venous thromboembolism, ischemic heart disease, arrhythmias,7,10 and heart failure 7,11.…”
Section: Introductionmentioning
confidence: 99%